DIGITAL ECONOMY: CONCEPTS AND DIRECTIONS OF DEVELOPMENT (Conferencea, 2022)
Theoretical foundations, stages, driving forces, efficiency factors of modern digitalization and the digital economy are considered. The key components of the term "digital economy" are presented: digital technologies, ecosystems and transformations, taking into account their interconnection and interdependence.